1989
DOI: 10.1007/bf02280186
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the molecular size of humic substances by organic acids of the root exudates

Abstract: A water solution of citric, malic, oxalacetic, succinic, fumaric acids at the concentration found in the root exudates of maize seedlings affected humic substances above 10 000 ds (HMS) by shifting their molecular size towards values below 10 000ds (LMS). The percent of LMS fraction obtained was significantly correlated with the release of Ca, Mg, Fe, and Zn. Addition of HC1 was ineffective on the molecular size, while the metal release occurred to a lesser extent. K salts of the organic acids were ineffective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 11 publications
(7 reference statements)
0
9
0
1
Order By: Relevance
“…The results presented here add to mounting evidence of an active role of plants in altering the root environment as a means of increasing the availability of nutrients, especially phosphorus, for absorption. Albuzio and Ferrari (1989) suggested that organic acids commonly found in root exudates can compete effectively with humic acids as ligands for metal, particularly at low pH. Among the peculiarities of rhizosphere soils, differences in nutrient availability with respect to the bulk soil have been emphasised (Marschner et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here add to mounting evidence of an active role of plants in altering the root environment as a means of increasing the availability of nutrients, especially phosphorus, for absorption. Albuzio and Ferrari (1989) suggested that organic acids commonly found in root exudates can compete effectively with humic acids as ligands for metal, particularly at low pH. Among the peculiarities of rhizosphere soils, differences in nutrient availability with respect to the bulk soil have been emphasised (Marschner et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Among the peculiarities of rhizosphere soils, differences in nutrient availability with respect to the bulk soil have been emphasised (Marschner et al, 1987). In addition to altering nutrient availability, changes in the humus molecular size, as an effect of organic acid release by roots, might influence regulatory signals between soil and plant by affecting the efficiency of transport systems in roots and stimulating or depressing enzyme activities involved in nutrient assimilation (Albuzio and Ferrari, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Since the plant root grows in contact with humic substances, some components of which can enter the cell, we should assume that cytoplasmic concentration of humic molecules may be limited, in order to avoid the detrimental effect at membrane level. This assumption seems to be reasonable in the light of previous results showing the capacity of the root to modulate the molecular size of humic substances by means of root exudates (Albuzio and Ferrari, 1989) and also considering the presence of the cell wall, which can act as a biological molecular filter toward humic molecules.…”
Section: Discussionmentioning
confidence: 92%
“…Attempts have been made to verify whether organic acids released by plant roots may change the structure of humic molecules (Albuzio and Ferrari, 1989 ). Analyses by size exclusion chromatography (SEC) have revealed that high -molecular -weight fractions treated with acidic solutions or organic acids release humic molecules of lower molecular weight with a higher biological activities than that of the former molecules.…”
Section: Humic Substances In the Rhizospherementioning
confidence: 99%